German history 1789-1871 : from the Holy Roman Empire to the Bismarckian Reich - Brose, Eric Dorn, 1948- (Berghahn Books, 2013)
During recent years, there has been a noticeable increase in interest in the nineteenth century, resulting in many fine monographs. However, these studies often gravitate toward Prussia or treat Germany's southern and northern regions as separate entities or else are thematically compartmentalized. This book overcomes these divisions, offering a wide-ranging account of this revolutionary century and skillfully combining narrative with analysis. Its lively style makes it very accessible and ideal for all students of nineteenth-century Germany.